2000
DOI: 10.1006/dbio.2000.9731
|View full text |Cite
|
Sign up to set email alerts
|

Role for cGATA-5 in Transcriptional Regulation of the Embryonic Chicken Pepsinogen Gene by Epithelial–Mesenchymal Interactions in the Developing Chicken Stomach

Abstract: A gene encoding embryonic chicken pepsinogen (ECPg), a zymogen of the digestive enzyme pepsin, is expressed specifically in epithelial cells of glands of embryonic stage proventriculus (glandular stomach) under the influence of mesenchyme. We found four GATA and one Sox binding motifs in 1.1 kb of the 5' flanking region of the ECPg gene which are essential to the organ-specific expression of the gene. The expression of cGATA-5 and cSox2 in the proventriculus from day 6 to day 12 of incubation was therefore ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 49 publications
3
48
1
Order By: Relevance
“…In vitro studies have shown that GATA-4 (or the closely related factors GATA-5 and -6) can bind and trans-activate several genes expressed in differentiating and terminally differentiated members of the parietal and zymogenic cell lineages (Tamura et al, 1993;Mushiake et al, 1994;Nishi et al, 1997;Sakamoto et al, 1998Sakamoto et al, , 2000, and studies with chimeric mice underscore the in vivo contributions of GATA-4 to expression of these genes (Jacobsen et al, 2002). In vitro, FOGs can either enhance or repress the activity of GATA-4, depending on the promoter studied (Lu et al, 1999;Viger, 2001, 2003;Lin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that GATA-4 (or the closely related factors GATA-5 and -6) can bind and trans-activate several genes expressed in differentiating and terminally differentiated members of the parietal and zymogenic cell lineages (Tamura et al, 1993;Mushiake et al, 1994;Nishi et al, 1997;Sakamoto et al, 1998Sakamoto et al, , 2000, and studies with chimeric mice underscore the in vivo contributions of GATA-4 to expression of these genes (Jacobsen et al, 2002). In vitro, FOGs can either enhance or repress the activity of GATA-4, depending on the promoter studied (Lu et al, 1999;Viger, 2001, 2003;Lin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…derm is required for endoderm differentiation (Weber et al, 1996;Reiter et al, 1999Reiter et al, , 2001Rodaway et al, 1999;Sakamoto et al, 2000;Afouda et al, 2005). In mice, chimera studies have shown that Smad2, a mediator of TGF-␤ signaling, is required for gut endoderm formation (Tremblay et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The apparatus used for electroporation of plasmid DNAs into PV epithelium was set up as follows (Sakamoto et al, 2000). Platinum electrodes were fixed on a glass dish and integrated into a resin chamber (7 mm in height, 8 mm in width and 5 mm in length).…”
Section: Transfection Of Plasmids Into Pv Epithelium By Electroporationmentioning
confidence: 99%
“…cRNA probes were generated by in vitro transcription from cDNA fragments of ECPg (Hayashi et al, 1988), chicken SP (Tabata and Yasugi, 1998), chicken Notch1, quail Serrate1, quail Delta1, chicken Numb (Wakamatsu et al, 1999;Wakamatsu et al, 2000), chicken Notch2, chicken Serrate2 [gifts from Dr R. Goistuka (Morimura et al, 2001)], chicken Hairy1, chicken Hairy2 [gifts from Dr O. Pourquié, (Palmeirim et al, 1997;Jouve et al, 2000)], chicken Smad8, Shh [gifts from Dr T. Nohno (Nohno et al, 1995;Ohuchi et al, 1997)], chicken Gata5 (Sakamoto et al, 2000), chicken Gata4, chicken Gata6 (Laverriere et al, 1994), chicken Sox2 (Ishii et al, 1998), chicken Sox21 (Uchikawa et al, 1999), chicken GK19 (Sato and Yasugi, 1997) and chicken Fra2 (Matsumoto et al, 1998).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…In chimeric mice produced from a high-percentage Gata4 null embryonic stem cells and a low percentage of wild-type embryonic stem cells, Gata4 ϩ/ϩ cells were observed only in visceral endoderm and gut endoderm at embryonic day 9 in embryos that were otherwise entirely derived from Gata4 Ϫ/Ϫ cells (56). GATA-4 is required for gastric epithelial differentiation during development (36), and gastric genes are activated by GATA factors in cultured cells (2,62,72). Gata5-deficient mice develop normally except for a defect in female genitourinary development and are healthy and fertile as adults (50), although an analysis of hepatic or gastrointestinal gene expression in these animals has not been reported.…”
mentioning
confidence: 99%